Adolescent close friendships, self-perceived social acceptance, and peer-rated likeability as predictors of wellbeing in young adulthood - Shah, Emily N.; Szwedo, David E.; Allen, Joseph P. (Frontiers in Developmental Psychology, 2024)
Introduction Links between interpersonal relationships and physical and psychological functioning have been well-established in the literature. During adolescence, success or distress in peer relationships may have distinct effects on different aspects of wellbeing. The present study aims to examine the ways in which different adolescent peer relationship contexts (i.e., close friendship quality, social acceptance, and likability from peers) can predict outcomes relevant to adult wellbeing (i.e., social anxiety, depression, aggression, social integration, romantic insecurity, job satisfaction, and physical health). Further, the study considers how different developmental stages of adolescence may impact links between peer relationships and wellbeing outcomes. Method Peer relationship contexts were assessed in early (ages 13–14) and late (ages 17–18) adolescence. Markers of wellbeing were measured in young adulthood (ages 28–30). A path analysis was used to examine whether the developmental timing of adolescent peer relationship contexts could predict wellbeing in young adulthood. Results Results suggest that, across adolescence, broader perceived social acceptance may be a more robust predictor of adult wellbeing compared to close friendship quality and peer likability. When examined at early and late adolescence separately, early adolescent social acceptance and late adolescent close friendship quality best predicted outcomes of adult wellbeing. Discussion Implications and considerations for future research are discussed.